011 Melbourne mobile stroke unit halves workflow for acute stroke reperfusion therapy. (29th July 2019) - Zhao, Henry; Coote, Skye; Langenberg, Francesca; Easton, Damien; Stephenson, Michael; Smith, Karen; Bernard, Stephen; Desmond, Patricia; Mitchell, Peter; Yan, Bernard; Campbell, Bruce CV; Parsons, Mark; et al.
Abstract : Background: The Melbourne Mobile Stroke Unit (MSU) utilises a specialised ambulance with on-board CT scanner and multidisciplinary team to provide on-scene imaging, treatment and triage for central Melbourne, Australia. We describe the operational impact of the MSU on commencement of acute reperfusion therapy. Methods: Data from the first 12 months of operation were collected for all patients receiving reperfusion therapy from November 2017. Workflow times were compared to contemporary published Australian data and historical controls from Royal Melbourne Hospital. Results: In the first calendar 12 months of operation, the Melbourne MSU operated 30.5 service weeks and provided prehospital thrombolysis (tPA) to n=52 patients (44% of eligible infarcts) and directed n=33 patients for endovascular thrombectomy, of which 48% required bypass from the closest non-thrombectomy hospital. The overall median onset-to-tPA for MSU patients was 97.5 mins compared to the Australian metropolitan median of 150 mins. Thrombolysis in the first 'golden hour' increased to 13.5% from 3.3% in-hospital. Median onset-to-groin for MSU patients receiving EVT was 162 mins compared to 234 mins from historical controls. Discussion: Prehospital treatment and triage using the Mobile Stroke Unit in metropolitan Melbourne resulted in substantial improvements in commencement of reperfusion therapy. Workflow times are approximately halved for thrombolysis and endovascular thrombectomy respectively. Prehospital thrombolysis also allowed a >400% increase in the proportion of treatment in the first 'golden hour'.